Granulocyte-macrophage colony-stimulating factor produced by splenic T lymphocytes of mice infected with Schistosoma japonicum. - Owhashi, M (1986)
The production of granulocyte-macrophage (GM) colony-stimulating factor (CSF) by splenic lymphocytes was examined in murine schistosomiasis japonica. When splenic lymphocytes obtained at various weeks after infection were cultured with soluble egg antigen, GM-CSF activity in the conditioned medium became detectable at 3 weeks after infection, reached a peak at week 5, and persisted at least up to week 7. Not only soluble egg antigen but also concanavalin A was highly effective in stimulating splenic lymphocytes to produce GM-CSF. When splenic lymphocytes were treated with anti-Thy-1.2 antibody and complement, GM-CSF-producing activity was completely abolished. The molecular weight of this T-cell-derived GM-CSF was estimated to be 30,000 by gel filtration on Sephadex G-150. After isoelectric focusing, GM-CSF activity was detected as two major peaks at pH 3.7 and 5.5. The physicochemical nature of this T-cell-derived GM-CSF was compared with those of known lymphokine GM-CSFs or with that of a previously reported GM-CSF in the serum of S. japonicum-infected mice (M. Owhashi and Y. Nawa, Infect. Immun. 49: 533-537, 1985).